DERAJAT KESEHATAN KUCING LIAR (Felis catus) MELALUI PEMERIKSAAN FUNGSI LIVER (SGPT DAN SGOT) DI PASAR KECAMATAN TEGALSARI KOTA SURABAYA - Era Hari Mudji; Lailia Dwi Kusuma Wardhani; Roeswandono Roeswandono; Nicodemos Borges Lonai (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2019)
The present research aims to know Stray cat health status in the Tegalsari sub-district market in Surabaya. This type of research is a descriptive study, experimental animals used were 30 stray cats on the market. Through examination of the liver function SGOT and SGPT. Blood serum Collection of Stray cat in three markets in central of Surabaya city, specifically in Tegalsari sub-district, namely the pasar kembang, pasar keputran selatan and pasar keputran utara, each market can take blood serum in 10 cats (Stray cat) as much as 3ml to test the value SGPT and SGOT, Data analysis using Analysis of Variant (ANOVA) the average value SGOT of Stray cat in pasar kembang 43.8+12.9 µ/l, pasar keputran selatan 79.0+ 50.3 µ/l and the pasar keputran utara 47.7+12.3 µ/l and average SGPT value on the Stray cat in the pasar kembang 98.0+48.7 µ/l, pasar keputran selatan 119.9+83.6 µ/l and pasar keputran utara 103,9+40.6 µ/l, especially the SGOT value can be significantly different (P<0.05) while the SGPT value is not significantly different (P>0.05). The value of SGOT and SGPT in pasar keputran selatan is higher compared to the pasar keputran utara and the pasar kembang.